STUDY OF THE OPERATION, MAINTENANCE, AND REPAIR SYSTEM OF THE BULGARIAN ARMED FORCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Support of armaments and equipment is an integral part of the overall system for logistical support of the armed forces, which in turn represents a complex set of elements and interrelationships implementing the logistical functions to meet the emerging needs of the army and the fulfillment of the intended missions, goals and tasks. The main elements in this system are the management bodies and forces for the implementation of maintenance and repair activities, and the qualification and training of the latter is of essential importance for the timely restoration of damaged samples of armaments and equipment in the conditions of time deficit. The paper aims to examin the state of the operation, maintenance and repair system in the Armed Forces of the Republic of Bulgaria. Based on an empirical study with the armaments and equipment maintenance and repair specialists at different hierarchical levels, main problems arise from the supply of material resources for service and repair and the chain of their supply, the training and education of technical personnel and unclear allocation of responsibilities and activities regarding maintenance and repair.